Scientific Validation of the IEC Specification for the Assessment and Characterization of Wave Resources using SWAN - Piché, Steffanie (Université d'Ottawa / University of Ottawa, 2024)
The research conducted in this study sought to appraise and validate the IEC-TC-114 technical specification for wave energy resource assessment in terms of its methodologies, requirements, and sources of error. This assessment was conducted through the pilot application of the IEC-TS to a project site located on the west coast of Vancouver Island in British Columbia. The objectives of this research were to (1) establish a firm scientific rational for the technical specification, (2) suggest improvements for future iterations of the technical specification, (3) conduct a sensitivity analysis to determine sources or error and uncertainty within the specification, (4) develop a user guidance , and (5) to complete an assessment of the wave energy resource for all three classes of assessment at the pilot project site. At the time of this research there has been limited assessment and validation of the technical specification and its applicability to real world studies. This study is also limited in its scope to a singular site within Canada and so specific observations made may not be applicable to all locations. It was observed over the course of this study that the IEC-TS could be applied to the assessment of wave energy with reasonable computational effort. Additionally, the IEC-TS is overall relatively easy to understand and apply, with the only exception to this being the validation procedure which lacked clarity. However, it was noted that in many cases the IEC-TS would not provide defined requirements, but only recommendations which would allow researchers to potentially disregard the recommendations provided within. While this is likely due to the fact that different sites may have different requirements, it does call into question the need for a standard if it is not going to have strict requirements to ensure that all resource assessments are completed using state of the art knowledge and procedures.
Keywords: Wave energy; Resource Assessment; numerical modelling